Apricot Production Forecast of the Leading Countries in The Period of 2018-2025. - Uzundumlu, Ahmet Semih; Karabacak, Tuba; Ali, Abdifatah (Emirates Journal of Food and Agriculture, 2021)
The aim of this study is to estimate apricot production quantities in 2018-2025 periods by using 1961-2017 data of the leading countries in apricot production in the world. 57-year data were obtained from FAOSTAT and analyzed with the help of the SAS 9.4 statistics program. In order to determine these predictions, ARIMA models have been used. In cases where the data is not stationary, the one-year delay was made and the most suitable ARIMA model was chosen according to AIC, BIC, SSE, MSE, MPE criteria. According to the 8-year average estimation based on 26 years of data, the share of countries in apricot production is formed by Turkey with 19%, Uzbekistan with 14%, Algeria with 7%, Iran with 6%, and Italy with 6%. Turkey ranked second after Spain in fresh apricot exports and first in the dried apricots although dried apricot export prices are less than Germany price currently, the government focusing on higher-quality types in fresh and dried apricots, France, and the Netherlands supplied dried apricots from Turkey.